2008
DOI: 10.1111/j.1365-2125.2008.03333.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical comparisons of diclofenac concentration in the soft tissues and blood plasma between topical and oral applications

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Efficacy of oral administration of nonsteroidal anti-inflammatory drugs (NSAIDs) on the synovial and muscle tissues has been established. • However, efficacy of percutaneous administration of NSAIDs has not sufficiently been established because of lack of scientific data. WHAT THIS STUDY ADDS• The diclofenac concentration in the muscle and fat at 12 h after topical application with a pair of tapes containing a total of 30 mg diclofenac sodium was significantly higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 9 publications
2
48
0
6
Order By: Relevance
“…However, due to the limited number of tendon samples, only a single concentration of each drug was tested in their study. Since the serum and soft tissue concentrations of DF after oral intake or topical application are reported to be seldom higher than 10 μM [33,34], further studies are needed to identify whether tendon detrimental effects could really happen following oral or topical application of DF. Up to know, the only in vivo study comes from Marsolais et al who found that the mechanical properties of injured rat Achilles tendons were identical in placebo and diclofenac-treated groups [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limited number of tendon samples, only a single concentration of each drug was tested in their study. Since the serum and soft tissue concentrations of DF after oral intake or topical application are reported to be seldom higher than 10 μM [33,34], further studies are needed to identify whether tendon detrimental effects could really happen following oral or topical application of DF. Up to know, the only in vivo study comes from Marsolais et al who found that the mechanical properties of injured rat Achilles tendons were identical in placebo and diclofenac-treated groups [35].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that diclofenac present in synovial fluid was not from direct penetration but from redistribution by systemic blood circulation. On the other hand, oral diclofenac showed significantly higher plasma concentration, synovial membrane tissue concentration and synovial fluid concentration, and also demonstrated better therapeutic efficacy than those by topical applications [7]. Additionally, topical diclofenac gel was only modestly effective against osteoarthritis pain in comparison to the placebo, since the placebo group also had substantial improvements in pain scores and function scores, possibly from the manual massage on the affected joint during application [8].…”
Section: Introductionmentioning
confidence: 99%
“…28 Based on these results, we may state that the anti-inflammatory effect of EUDPCL-T device may have been favored by the controlled release of the drug to the joint, favoring the diffusion to the joint capsule, and thence to the membrane and synovial fluid, where there is known affinity with sodium diclofenac and where the site of the drug action is located. 29 Figure 4 shows that DICL groups tended to have edema reduction when compared with CRGN groups, but no statistically significant difference was found (p <0.05). The EUDPCL-T group showed a statistically significant edema reduction compared with the CRGN group.…”
Section: Anti-inflammatory Activity Of Implanted Devicementioning
confidence: 95%